2013
DOI: 10.1002/jsfa.6241
|View full text |Cite
|
Sign up to set email alerts
|

1H and13C NMR-based sugar profiling with chemometric analysis and antioxidant activity of herbhoneys and honeys

Abstract: Herbhoneys have similar antioxidant properties to traditional honeys, being therefore of equal nutritional value. There was a noticeable influence of the extract concentration on the observed antioxidant effect. For samples with high antioxidant activity, polyphenols were responsible for the observed effect. Sample clustering due to sucrose content in the NMR-PCA study allowed effortless detection of adulteration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 40 publications
2
23
0
1
Order By: Relevance
“…Results obtained for herbhoneys ranged from 37.01 for pine to 48.36 mg/100 g for nettle sample and were in good correlation with results of Socha et al (2009). It should be emphasized that other authors have found higher amounts of phenolic compounds in nettle (~110 mg/100 g), pine (~70 mg/100 g) and especially in hawthorn herbhoney (~190 mg/100 g) (Jamr oz et al, 2014). It was found that p-coumaric acid is the main constituent of herbhoneys (Isidorov et al, 2015;Socha et al, 2009).…”
Section: Antioxidant Properties and Total Phenolic Contentsupporting
confidence: 76%
See 1 more Smart Citation
“…Results obtained for herbhoneys ranged from 37.01 for pine to 48.36 mg/100 g for nettle sample and were in good correlation with results of Socha et al (2009). It should be emphasized that other authors have found higher amounts of phenolic compounds in nettle (~110 mg/100 g), pine (~70 mg/100 g) and especially in hawthorn herbhoney (~190 mg/100 g) (Jamr oz et al, 2014). It was found that p-coumaric acid is the main constituent of herbhoneys (Isidorov et al, 2015;Socha et al, 2009).…”
Section: Antioxidant Properties and Total Phenolic Contentsupporting
confidence: 76%
“…The different types of herbhoneys have different functional effects depending on the types of raw materials used in their production. In Poland they are used in phytotherapy as prophylactic agents and nutritional supplements (Juszczak, Socha, Ro _ znowski, Fortuna, & Nalepka, 2009;Kę dzia & Kostrzewski, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore it also can uncover the relationships between observations and variables and between the variables themselves [16,17]. In turn, the PCA has been widely applied in diverse areas of investigation [1820,15,21,22]. …”
Section: Introductionmentioning
confidence: 99%
“…From fraction FB, a mixture of D-glucopyranose (2), β-Dglucopyranose (3), β-D-fructopyranose (4), α-D-fructofuranose (5), and β-D-fructofuranose (6) was identified by comparing the data of 1 H and 13 C NMR with those described in the literature ( Fig. 3 and Table 2) (Asaoka, 1983;Funcke & Klemer, 1976;Jamroz et al, 2014). This fraction was analyzed by UHPLC-ELSD, which resulted in isolation of D-fructose (2 + 3), D-glucose (4 + 5 + 6), and sucrose (1), whose retention times were compared with authentic standards (Fig.…”
Section: Determination Of the Major Chemical Compositionmentioning
confidence: 99%